Whole genome sequencing and phylogenetic analysis of feline anelloviruses - Jarošová, Veronika; Hrazdilová, Kristýna; Filipejová, Zita; Schánilec, Pavel; Celer, Vladimír (Infection, genetics and evolution, 2015)
Torque teno felis virus (FcTTV) was detected in the cat population in the Czech Republic. A total of 110 serum samples were tested by a nested PCR technique using specific primers, situated in the highly conserved untranslated region of the virus genome. The frequency of feline TT virus in the Czech Republic was found to be 33.63%. Sequencing of PCR product from several virus strains showed that all of them are closely related and belong to the same virus species. Whole genome sequencing of three strains was performed to compare overall genetic heterogeneity of feline TT viruses. One of these three strains showed more that 10% difference at the nucleotide level. Furthermore we didn't find any correlation between FcTTV infection and sex or health status of examined animals.
Keywords: prevalence; Cats; fylogeneze; Viral Proteins; genom virový; Česká republika; Prevalence; zvířata; Cat Diseases; infekce DNA virem; polymerázová řetězová reakce; Animals; Polymerase Chain Reaction; DNA Virus Infections; Phylogeny; nemoci koček; Czech Republic; Genome, Viral; virové proteiny; Torque teno virus; kočky